Strategi Pemasaran Tahu Sukawati di Desa Sukawati Kecamatan Sukawati Kabupaten Gianyar - WIBAWA, ANAK AGUNG NGURAH SURYA YUDA PRATAMA; WIJAYANTI, PUTU UDAYANI; WIBAWA, MADE SATRIA (Jurnal Agribisnis dan Agrowisata (Journal of Agribusiness and Agritourism); Vol.13, No.1, November 2024, 2024)
Marketing Strategy to Sukawati Tofu in Sukawati Village Sukawati District Gianyar Regency. This research is carried out with the aim of knowing the internal and external factors of the usaha Tahu Sukawati. The existence of this research is to review directly how a business can survive in a strict business. This research directly analyzes how manufacturers and distributors can connect with each other. This research uses a qualitative method, which is a method used to understand something that is analyzed descriptively. The qualitative method explains a topic in depth and collects complete data. The qualitative method in this research focuses more on the business elements that are analyzed as well as the role of humans in the business of usaha Tahu Sukawati. As for the result of this research, the business of usaha Tahu Sukawati can survive very well when viewed from internal and external factors of the business. In addition, the marketing strategy usaha Tahu Sukawati by establishing cooperative cooperation with agents, making this business have an effective strategy in market competition. The cooperation between business owners and agents makes the business know that usaha Tahu Sukawati has regular customers in business activities. The conclusion of this research is that usaha Tahu Sukawati is very consistent in doing business activities. Usaha Tahu Sukawati always prioritizes product quality and customer satisfaction. However, to develop this business to be more advanced, usaha Tahu Sukawati should add to the marketing strategy by following the development of existing technology, so that this business will continue to advance to follow the existing business flow.